2008
DOI: 10.1017/s175173110800219x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of leptin gene polymorphism on the breeding value of milk production traits in Iranian Holstein

Abstract: New molecular techniques focused on genome analysis, open new possibilities for more accurate evaluation of economiclly important traits in farm animals. Milk production traits are typical quantitative characteristics controlled by a number of genes. Mutations in their sequences may alter animal performance as well as their breeding values. In this study, we investigated the effect of Kpn2I restriction fragment length polymorphisms in the leptin gene, on bull breeding values for milk yield, fat, and protein yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 14 publications
1
5
0
4
Order By: Relevance
“…The distribution of LEP gene polymorphism in local, cross and Holstein Frisian bovines was estimated, using Chi-square test (Table 4). These findings were similar to those previously reported for Holstein Frisian cows [11], Iranian native, Holstein and Brown Swiss cows [12], Sahiwal and Frieswal cattle [13] as well as Holstein primiparous cows [14]. [15], reported that the most frequent homozygotes genotypes was BB, throughout their studying on Chinese indigenous cattle , and this is may be due to the nature of their race or breeds cattle population.…”
Section: Resultssupporting
confidence: 90%
“…The distribution of LEP gene polymorphism in local, cross and Holstein Frisian bovines was estimated, using Chi-square test (Table 4). These findings were similar to those previously reported for Holstein Frisian cows [11], Iranian native, Holstein and Brown Swiss cows [12], Sahiwal and Frieswal cattle [13] as well as Holstein primiparous cows [14]. [15], reported that the most frequent homozygotes genotypes was BB, throughout their studying on Chinese indigenous cattle , and this is may be due to the nature of their race or breeds cattle population.…”
Section: Resultssupporting
confidence: 90%
“…Respon energi yang meningkat menyebabkan terjadinya penghancuran sel trigliserida dalam jaringan lemak sebagai upaya untuk melepaskan asam lemak bebas yang digunakan untuk proses oksidasi dalam metabolisme tubuh (Denver et al 2011 (Moussavi et al 2006), Sistani (Nobari et al 2010), Sarabi (Javanmard et al 2008), Golpayegani, Taleshi (Nahavandi et al 2010), Mazandarani, Dashtiyari (Javanmard et al 2005), Fries Holstein (Liefers et al 2002), lokal Irak (Hussain et al 2017), Slovak Spotted dan Pinzgau (Trakovická et al 2013). Polimorfisme pada bagian ekson 2 gen leptin (Lep/Kpn2I) dilaporkan terjadi pada sapi Golpayegani, Taleshi, Sarabi, Sistani, Fries Holstein dan Brown Swiss (Nassiry et al 2008), Iranian Holstein (Sadeghi et al 2008), Frieswal, Ongole, Sahiwal (Singh et al 2014) dan Polish Holstein-Friesian (Komisarek 2010;Moravcikova et al 2012), Hanwoo (Kong et al 2006), Jersey, Hariana, Sahiwal, Gir dan Nimari (Choudhary et al 2005). Selain itu, polimorfisme pada ekson 2 gen leptin (Lep/ClaI) dilaporkan terjadi pada beberapa bangsa sapi B. taurus (Lagonigro et al 2003) sedangkan polimorfisme pada gen leptin (Lep/HphI) dilaporkan terjadi pada beberapa bangsa sapi potong dan perah (Almeida et al 2003;Choudhary et al 2006;Komisarek 2010).…”
Section: Struktur Gen Leptin Dan Mekanisme Kerja Hormon Leptinunclassified
“…Polimorfisme pada bagian ekson 3 gen leptin (Lep/BsaAI) dilaporkan terjadi pada sapi Bali (Syarifulaya et al 2015), Friesian Holstein (Azari et al 2012), Nelore (Curi et al 2011), Jersey, Hariana, Sahiwal, Gir dan Nimari (Choudhary et al 2005). Polimorfisme di bagian ekson 3 pada gen leptin (Lep/NruI) dilaporkan terjadi pada sapi B. taurus (British Friesian, Aberdeen Angus, Hereford, Highland, Charolais (Lagonigro et al 2003), Iranian Holstein (Sadeghi et al 2008), Golpayegani, Najdi, Sarabi, Sistani (Aslaminejad et al 2010), Frieswal, Ongole dan Sahiwal (Singh et al 2014). Kong et al (2006)…”
Section: Struktur Gen Leptin Dan Mekanisme Kerja Hormon Leptinunclassified
“…En ganadería, tales variaciones en el ADN también pueden estar asociadas con, o ligadas a los rasgos económicos, que son gobernados por muchos genes, cada uno con un pequeño efecto (1) . Esos genes principales suelen estar involucrados en la biología de un rasgo, y son los genes candidatos para identificar marcadores (2) . También existe la posibilidad de que genes mayores puedan estar relacionados con algunos loci de rasgos cuantitativos (QTL), contribuyendo a la mayor parte de la variación en los rasgos.…”
Section: Introduccionunclassified
“…In livestock, such variations in DNA may also be associated with, or linked to, economic traits, which are governed by many genes each having a small effect (1) . Those major genes being usually involved in the biology of a trait and they are the candidate genes for marker identification (2) . There is also the possibility that major genes may be linked with some quantitative trait loci (QTL) contributing to a major part of the variation in traits.…”
Section: Introductionmentioning
confidence: 99%